High-frequency plastid transformation in tobacco by selection for a chimeric aadA gene. - Svab, Z (1993)
We report here a 100-fold increased frequency of plastid transformation in tobacco by selection for a chimeric aadA gene encoding aminoglycoside 3"-adenylyltransferase, as compared with that obtained with mutant 16S rRNA genes. Expression of aadA confers resistance to spectinomycin and streptomycin. In transforming plasmid pZS197, a chimeric aadA is cloned between rbcL and open reading frame ORF512 plastid gene sequences. Selection was for spectinomycin resistance after biolistic delivery of pZS197 DNA into leaf cells. DNA gel-blot analysis confirmed incorporation of the chimeric aadA gene into the plastid genome by two homologous recombination events via the flanking plastid gene sequences. The chimeric gene became homoplasmic in the recipient cells and is uniformly transmitted to the maternal seed progeny. The ability to transform routinely plastids of land plants opens the way to manipulate the process of photosynthesis and to incorporate novel genes into the plastid genome of crops.